SIMULATION AND PROTOTYPE DESIGN OF HYBRID RENEWABLE ENERGY HARVESTING SYSTEM - MUHAMMAD SYUKRI BIN NURULHAK, - (Universiti Malaysia Sarawak, 2022)
In this era of globalization, the energy harvesting technology for renewable energy has improved to combat the concern in energy conservation, global warming, and excessive waste materials. Additionally, the problem of getting continuous and reliable energy and power supply will become a real issue in the future. The energy harvesting technology can be an alternative to the current power generation and can lead to a potential of getting more reliable power supply for everyone. By combining multiple renewable energy harvesting system, more power can be continuously generated, and the efficiency of energy output will increase. This paper focus on the development of hybrid renewable energy harvester system consists of photovoltaic, piezoelectric and wind energy. The performance and the capabilities of the system are recorded are analyse under different conditions and parameters.